Investigation of the machinability of the Al 7075 alloy using DLC coated cutting tools - (:unkn) unknown (ACADEMIC JOURNALS, 2011)
Aluminum and aluminum alloys are vital to the aerospace industry. They are of great significance to other areas of transportation and building in which durability, strength and light weight are required. In this study, an experimental investigation on surface roughness, cutting temperature and cutting forces in turning of aluminum 7075 alloy using diamond like carbon (DLC) coated cutting tools was presented. The effects of the feed rate, cutting speed and depth of cut on surface roughness, cutting temperature and cutting force were examined. In order to optimize the experimental results, Taguchi optimization method was employed. The effect of each parameter on the obtained results was determined by the use of analysis of variance (ANOVA). The relationship between dependent and independent parameters was modelled with regression analysis. The optimal machinability of Al 7075 alloy with DLC coated insert was successfully determined in this study.
Keywords: Aluminum 7075; DLC coated inserts; machinability; Taguchi optimization method; analysis of variance (ANOVA); regression analysis; CARBON-FILMS; COATINGS; WEAR; FRICTION; FORCE